Investigating the Organization of Zakat in Iran with Emphasis on Zakat Law and Regulations - Hosin Hasanzadeh Sarvestani; Alireza Etemadifar (تحقیقات مالی اسلامی (پیوسته))
The Zakat Organization manages the mobilization and allocation of Zakat assets based on the Zakat Law and Regulations. The Zakat Law was approved in 1390 and its regulations in 1402. The main structure of the Central Zakat Council and its duties, incentive policies, and the presence of the Zakat Council in the country's divisions are specified in the law, and the functioning of the aforementioned structure is determined in the executive regulations. Despite the attention of the relevant authorities, this organization faces challenges that can be examined in different dimensions. In this study, using the meta-synthesis method, the challenges of the Zakat Organization were extracted through the analysis of the works of researchers and were examined in a comparative manner with the provisions of the Zakat Law and Regulations. The purpose of the comparative study is to examine the position (response or silence) of the Zakat Law and its regulations regarding the challenges raised. The organizing themes of the challenges of zakat organization in Iran are: fundamental and theoretical, financing from the budget, cultural and educational, structural, executive, regulatory and supervisory. A total of twenty-six challenges (basic themes) were identified and placed under the aforementioned categories (organizing themes). Each of them, the research and the results of the researchers are described under each of them.